Accounting for frailty and multimorbidity when interpreting high‐sensitivity troponin I tests in oldest old. Issue 2 (18th November 2021) - Ticinesi, Andrea; Nouvenne, Antonio; Cerundolo, Nicoletta; Prati, Beatrice; Parise, Alberto; Tana, Claudio; Rendo, Martina; Guerra, Angela; Meschi, Tiziana
Abstract: Background: Older patients evaluated in Emergency Departments (ED) for suspect Myocardial Infarction (MI) frequently exhibit unspecific elevations of serum high‐sensitivity troponin I (hs‐TnI), making interpretation particularly challenging for emergency physicians. The aim of this longitudinal study was to identify the interaction of multimorbidity and frailty with hs‐TnI levels in older patients seeking emergency care. Methods: A group of patients aged≥75 with suspected MI was enrolled in our acute geriatric ward immediately after ED visit. Multimorbidity and frailty were measured with Cumulative Illness Rating Scale (CIRS) and Clinical Frailty Scale (CFS), respectively. The association of hs‐TnI with MI (main endpoint) was assessed by calculation of the Area Under the Receiver‐Operating Characteristic Curve (AUROC), deriving population‐specific cut‐offs with Youden test. The factors associated with hs‐TnI categories, including MI, CFS and CIRS, were determined with stepwise multinomial logistic regression. The association of hs‐TnI with 3‐month mortality (secondary endpoint) was also investigated with stepwise logistic regression. Results: Among 268 participants (147 F, median age 85, IQR 80–89), hs‐TnI elevation was found in 191 cases (71%, median 23 ng/L, IQR 11–65), but MI was present in only 12 cases (4.5%). hs‐TnI was significantly associated with MI (AUROC 0.751, 95% CI 0.580–0.922, p = 0.003), with an optimal cut‐off of 141 ng/L. hs‐TnI levels ≥141 ng/L were significantly associated with CFS (OR 1.58, 95% CI 1.15–2.18, p = 0.005), while levels <141 ng/L were associated with the cardiac subscore of CIRS (OR 1.36, 95% CI 1.07–1.71, p = 0.011). CFS, but not hs‐TnI levels, predicted 3‐month mortality. Conclusions: In geriatric patients with suspected MI, frailty and cardiovascular multimorbidity should be carefully considered when interpreting emergency hs‐TnI testing.